Rare plant restoration on Long Pine Key - Holst, Bruce; Daltröm, Stig (Lankesteriana: International Journal on Orchidology, 2015)
The Long Pine Key area of Everglades National Park (Florida) is critical habitat for a large number of rare plant species including two candidates for federal listing and several dozen listed as endangered or threatened by the state of Florida. In addition, there are nineteen species present in the Long Pine Key area that are critically imperiled in South Florida and six species historically documented from the area that may be extinct in the continental United States (Gann et al., 2002).